SOME BOHR-TYPE INEQUALITIES FOR SENSE-PRESERVING HARMONIC MAPPINGS - I. S. Amusa; A. A. Mogbademu (Проблемы анализа)
In this paper, we investigate the Bohr-type radii for various forms of Bohr-type inequalities for the sense-preserving har- monic mapping of the form $f(z) = h(z) + \overline{g(z)}$.